Intraspecific variability of leaf form and function across habitat types - Giacomo Puglielli; Alessandro Bricca; Stefano Chelli; Francesco Petruzzellis; Alicia T. R. Acosta; Giovanni Bacaro; Eleonora Beccari; Liliana Bernardo; Gianmaria Bonari; Rossano Bolpagni; Francesco Boscutti; Giacomo Calvia; et al. (Ecology Letters, 2024)
Trait‐based ecology has already revealed main independent axes of trait variation defining trait spaces that summarize plant adaptive strategies, but often ignoring intraspecific trait variability (ITV). By using empirical ITV‐level data for two independent dimensions of leaf form and function and 167 species across five habitat types (coastal dunes, forests, grasslands, heathlands, wetlands) in the Italian peninsula, we found that ITV: (i) rotated the axes of trait variation that define the trait space; (ii) increased the variance explained by these axes and (iii) affected the functional structure of the target trait space. However, the magnitude of these effects was rather small and depended on the trait and habitat type. Our results reinforce the idea that ITV is context‐dependent, calling for careful extrapolations of ITV patterns across traits and spatial scales. Importantly, our study provides a framework that can be used to start integrating ITV into trait space analyses.